VALIDATION OF THE ANALYTICAL METHOD FOR THE DETERMINATION OF DEXKETOPROFEN TROMETHAMINE AS A RESIDUAL SUBSTANCE. SPECIFICITY, ACCURACY, LINEARITY, REPEATABILITY, DETECTION LIMIT AND QUANTITATION LIMIT OF THE METHOD - I.K. Saburov; N.A. Yunuskhodjayeva; Saburov Ilkhom Komilovich; Yunuskhodjayeva Nodira Abdulkhamitovna (Western European Studies, 2024)
In this article, validation of the developed new analytical method by High Performance Liquid Chromatography (HPLC) method was carried out, which developed for determination of the dexketoprofen tromethamine as residual substance in the injectable pharmaceutical plant during the cleaning validation. First of all, all products of injectable plant were divided to groups according to their pharmacology and chemical characteristics. Then Maximum Allowable Carryover (MAC or MACO) was calculated for all products. Target of the scientific work was developing new analytical methods for the non-steroidal anti-inflammatory injectable products in injectable plant. One of the non-steroidal anti-inflammatory injectable products was dexketoprofen tromethamine. That is why, new HPLC method was developed for determination of MACO quantity of same substance. Validation of the new developed analytical method was done according to guidelines of European medicines agency (EMEA) and international conference on harmonization of technical requirements for registration of pharmaceuticals for human use (ICH). In accordance with the requirements of the guidelines, validation was carried out according to the following parameters for the validation of analytical methods, like specificity, accuracy, linearity, repeatability, detection limit and quantitation limit of the method
Keywords: analytical methods; validation; specificity; accuracy